Do operating profits induce a wage premium equally shared among employees earning high or low incomes? - Jarle Aarstad; Olav A. Kvitastein (Economies, 2021)
Panel data show that between 2001 and 2014 Norwegian industries' increasing aggregated operating profits per employee increased average wages and wage inequality. The data imply that increasing profits, perhaps unsurprisingly, induce a wage premium. The data further imply that employees earning high incomes at the outset had the highest wage increase percentage-wise. Decreasing operating profits per employee had opposite but less robust effects on average wages and wage inequality. Panel data Granger causality tests finally showed that average wages, but not wage inequality, reversely and positively affect operating profits per employee.
Keywords: 330; average wages; causality; Gini-coefficients; operating profits; performance; productivity; wage inequality